Validating the danger of vehicular protective devices and bowel injury. Issue 9 (September 2022) - Abid, Mustafa; Schneider, Andrew; Raff, Lauren; Charles, Anthony; Gallaher, Jared R
Highlights: Small bowel or colon injuries after motor vehicle collision occur in about 1% of patients. The adjusted odds ratio of undergoing bowel resection or repair when wearing a seat belt is 2.09 (95% CI 1.91, 2.28). Airbag deployment and seatbelt use combined confer an adjusted OR of 3.27 (95% CI 3.02, 3.54) for bowel repair/resection. Seat belt use is associated with significant protection from death with an adjusted OR of 0.50 (95% CI 0.48, 0.53). Abstract: Introduction: Protective devices such as seat belts and airbags have improved the safety of motor vehicle occupants, but limited data suggest they may be associated with increased blunt bowel (small bowel or colon) injuries (BI). Unfortunately, this risk is unquantified. Methods: We analyzed the National Trauma Data Bank (2017-2019) using ICD-10 codes to identify adult motor vehicle occupants with BI who underwent surgical repair. We used logistic regression modeling to compare the risk of undergoing surgical repair for BI after using a protective device. Results: Of 2, 848, 592 injured patients, 475, 546 (16.7%) were motor vehicle occupants. Only 1.2% ( n = 5627/475, 546) of patients underwent a bowel repair or resection. Using a seat belt only was associated with an adjusted OR of 2.09 (95% CI 1.91, 2.28) for undergoing a bowel repair/resection when adjusting for Injury Severity Score (ISS) and age. Airbag deployment without a seat belt had an adjusted OR of 1.46 (95% CI 1.31, 1.62), while both devices combined conferred an OR of 3.27 (95% CI 3.02, 3.54). However, using a seat belt was protective against death with an OR of 0.50 (95% CI 0.48, 0.53), adjusted for age, sex, Charlson Comorbidity Score, and ISS. Conclusion: Seat belts and airbags are essential public health safety interventions and protect against death in motor vehicle-associated injuries. However, patients involved in MVCs with airbag deployment or while wearing a seat belt are at an increased risk of bowel injury requiring surgery compared to unrestrained patients, despite these events being relatively uncommon.